A NUMERICAL METHOD FOR SOLVING A TWO-DIMENSIONAL DIFFUSION EQUATION WITH NON LOCAL BOUNDARY CONDITIONS (Sciences & Technology. A, exactes sciences, 2011)
This paper is devoted to the decomposition method which is applied to solve problems with non local boundary conditions. The analytic solution of the problem is calculated in a series form with easily computable components. The comparison of   the methodology with some known techniques shows that the present approach is powerful, efficient and reliable.